Ettinoentomological knowledge documentation of indigenous people in Peninsular Malaysia - Nurul Ashikin Ismail; Maryati Mohamed (Pusat Sistematik Serangga ,UKM, 2014)
Ethnoentomological knowledge can be defined as information and practices used by different human culture that are related to insects. Documentation of the knowledge is essential as it may lead to exploration of other fields. In Malaysia, documentation of the knowledge is very limited albeit indigenous people have been using insects in their daily life for ages. It is interesting to note that insects have not been procured only for food but also as medicines and for other uses. However, throughout this research it is evident that the knowledge has begun to erode as the indigenous people moved towards modernisation. This paper focuses on the issues and challenges faced by researchers when performing the documentation processes.